2016
DOI: 10.1007/s00270-016-1309-2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Intractable Postpartum Hemorrhage Caused by Vaginal Laceration

Abstract: Postpartum hemorrhages caused by vaginal lacerations involve the vaginal artery arising from the anterior trunk of the internal iliac artery with various branching patterns. Superselective vaginal artery embolization is clinically acceptable for the successful treatment of vaginal laceration hemorrhages, with no complications. After vaginal artery embolization, it is suggested to check for the presence of other possible bleeding vessels by pelvic aortography with a catheter tip at the L3 vertebral level, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
7
0
4
Order By: Relevance
“…Based on the retrospective review of the angiographic finding, the consensus was that additional uterine arterial embolization was unnecessary even in this patient. According to previous reports of PPH from birth canal injury, bleeding could be successfully controlled by super-selective target arterial embolization without uterine artery embolization (18,19). Therefore, it would be desirable to make more efforts to find causative non-uterine arteries when the PPH is not due to uterine atony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the retrospective review of the angiographic finding, the consensus was that additional uterine arterial embolization was unnecessary even in this patient. According to previous reports of PPH from birth canal injury, bleeding could be successfully controlled by super-selective target arterial embolization without uterine artery embolization (18,19). Therefore, it would be desirable to make more efforts to find causative non-uterine arteries when the PPH is not due to uterine atony.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complex pelvic arterial anatomy and the potential vascular anastomotic network around the uterus, non-uterine pelvic arteries are also possible sources of PPH (6). Moreover, non-uterine arteries are major sources of PPH in certain clinical situations such as cases of birth canal laceration (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The use of permanent embolic materials in many cases of S-TAE may also be related, although embolic materials were not related to the failure of bleeding control in the previous report [8]. We used NBCA for about half of the patients in this study, which is more frequent than previously reported [8][9][10]. Several studies have reported that TAE using NBCA was effective to prevent recanalization, particularly in cases of pseudoaneurysm or active bleeding with extravasation [15,16].…”
Section: Discussionmentioning
confidence: 69%
“…However, intractable PPH due to GTT, where hemostasis by sutures is difficult to achieve, does not require bilateral UAE but rather transcatheter arterial embolization (TAE) of the bleeding point. Several studies have demonstrated the high effectiveness of TAE for intractable PPH due to GTT [8][9][10]. However, some reports have suggested that the blood vessels that cause bleeding due to GTT are diverse, and there is a risk of re-bleeding from anastomotic branches [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…AEM has been reported as a reliable therapeutic option for PPH, especially for cases of PGHA in which hemostasis cannot be achieved by CM or SURG (Hsu and Wan 1998;Pelage et al 1998;Villella et al 2001;Banovac et al 2007;Baruch et al 2015;Soyer et al 2015;Koganemaru et al 2016; Committee on Practice Bulletins-Obstetrics 2017; Lee et al 2018). Moreover, the efficacy of AEM as the initial treatment for PGHA has recently been reported (Distefano et al 2013;Takagi et al 2017).…”
Section: Discussionmentioning
confidence: 99%